Loss of end‐differentiated β‐cell phenotype following pancreatic islet transplantation. Issue 3 (17th October 2017) - Anderson, S. J.; White, M. G.; Armour, S. L.; Maheshwari, R.; Tiniakos, D.; Muller, Y. D.; Berishvili, E.; Berney, T.; Shaw, J. A. M.
Abstract : Replacement of pancreatic β‐cells through deceased donor islet transplantation is a proven therapy for preventing recurrent life‐threatening hypoglycemia in type 1 diabetes. Although near‐normal glucose levels and insulin independence can be maintained for many years following successful islet transplantation, restoration of normal functional β‐cell mass has remained elusive. It has recently been proposed that dedifferentiation/plasticity towards other endocrine phenotypes may play an important role in stress‐induced β‐cell dysfunction in type 2 diabetes. Here we report loss of end‐differentiated β‐cell phenotype in 2 intraportal islet allotransplant recipients. Despite excellent graft function and sustained insulin independence, all examined insulin‐positive cells had lost expression of the end‐differentiation marker, urocortin‐3, or appeared to co‐express the α‐cell marker, glucagon. In contrast, no insulin + /urocortin‐3 − cells were seen in nondiabetic deceased donor control pancreatic islets. Loss of end‐differentiated phenotype may facilitate β‐cell survival during the stresses associated with islet isolation and culture, in addition to sustained hypoxia following engraftment. As further refinements in islet isolation and culture are made in parallel with exploration of alternative β‐cell sources, graft sites, and ultimately fully vascularized bioengineered insulin‐secreting microtissues, differentiation status immunostaining provides a novel tool to assess whether fully mature β‐cell phenotype has been maintained. Abstract : This study reports loss of end‐differentiated pancreatic β‐cell phenotype despite excellent graft function following clinical intraportal islet transplantation.